Enhancing Employee Performance through Strengthened Knowledge Management, Training, and Work Engagement: Evidence from the Financial and Development Supervisory Agency : - Ade Nasir; Nancy Yusnita; Herdiyana (Asosiasi Ahli Administrasi Indonesia, 2026)
This study explores the role of knowledge management and training in improving employee performance by considering work engagement as an intervening mechanism within a public sector supervisory institution. The research adopts a quantitative approach and involves civil servants working at a regional financial and development supervisory agency in Indonesia. Data were obtained through standardized and reliable measurement instruments, and the relationships among variables were analyzed using a causal modeling technique. The findings indicate that both knowledge management and training play an important role in strengthening work engagement and enhancing employee performance. These results suggest that employee performance is shaped not only by the development of knowledge and skills but also by the level of psychological involvement and enthusiasm employees bring to their work. From a practical perspective, the study highlights the importance for public sector organizations to develop integrated knowledge management practices and deliver effective training programs while simultaneously fostering employee engagement. The originality of this study lies in confirming the mediating role of work engagement, demonstrating the complementary influence of knowledge management and training, and providing empirical evidence.